INTELEKTUALITAS, GAIRAH & KERENDAHAN HATI: SIKAP TERHADAP SAINS DAN TEKNOLOGI [INTELLECTUALITY, PASSION & HUMILITY: ATTITUDES TOWARDS SCIENCE AND TECHNOLOGY] - Ihan Martoyo; Eric Jobiliong; Wiryanto Dewobroto; Ukur Sembiring; Setiawan Sutanto; Rudy Hartono (Universitas Pelita Harapan, 2019)
Some would claim that science and technology contradict the life of faith, or that the one is more important or higher than the other. Such dualism/dichotomy may result from the pressure of atheism or the friction between various convictions in which scientists work. This writing suggests a healthier attitude towards science and technology for people of faith, where science, technology, and faith are approached without the crippling sacred/secular dichotomy. The concept of cultural mandate (Kuyper) provides a model for cultivating intellectuality, passion and humility as a divine mandate in faithful stewardship towards nature. A well-rounded scientist or engineer must be also aware of the ethical challenges in his or her field.BAHASA INDONESIA ABSTRAK: Ada yang mengklaim bahwa sains dan teknologi berkontradiksi dengan kehidupan iman, atau bahwa yang satu lebih penting atau lebih tinggi dari yang lain. Dualisme/dikotomi demikian dapat muncul dari tekanan paham ateisme atau gesekan dari berbagai keyakinan tempat ilmuwan beraktivitas. Tulisan ini mengusulkan suatu sikap yang lebih sehat terhadap sains dan teknologi untuk orang percaya, di mana sains, teknologi dan iman didekati tanpa dikotomi sakral/sekuler yang melumpuhkan. Konsep mandat budaya (Kuyper) menyediakan model untuk mengusahakan intelektualitas, gairah & kerendahan hati sebagai mandat ilahi dalam penatalayanan yang setia kepada alam. Seorang ilmuwan atau insinyur yang lengkap juga harus peka pada berbagai tantangan etika dalam bidangnya.